Ríos vs. fronteras - Aníbal Cetrangolo (Les Cahiers ALHIM)
Immigrant communities, mainly Italian, have built opera houses on the banks of South American navigable waterways. The existence of these theaters allows us to suppose a very specific type of lyrical circulation. The same operas crossed the borders of Argentina, Uruguay and Brazil. An international audience participated of the same lyrical season. This activity contrasted the nationalistic will to build a "national identity" through operatic phenomena. Important international artists have performed in those riverside theaters. These theaters show a representative character very different from that of the capital's opera houses: while the Teatro Colón, Teatro Solís, Teatro Municipal de Santiago or Teatro Municipal de Rio de Janeiro represented the country, the provincial theaters were a bridge with a very distant world. To analyze the link among the longing for international openness in a place far from the centers of power, it has been chosen to study a specific case, that of the Teatro Aguiar built in the southern part of the Paraná River.